Pendampingan Penguatan Nilai-nilai Moderasi Beragama Melalui Pemahaman Al-Qur’an terhadap Guru-guru TPQ Kota Cirebon - Umayah Umayah; Muhammad - Maimun; Nurkholidah Nurkholidah; Mumun Munawaroh (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
ASSISTANCE IN STRENGTHENING THE VALUES OF RELIGIOUS MODERATION THROUGH UNDERSTANDING THE QUR'AN FOR TPQ TEACHERS IN CIREBON CITY. This service is an assistance to TPQ teachers in the city of Cirebon related to understanding the Qur'an about the values of religious moderation. Moderation values need to be instilled, especially in the field of education. Indicators and keywords of religious moderation, especially in relation to understanding the Qur'an, have not been fully understood by TPQ teachers in the city of Cirebon. Based on PPMI research, 57% of Islamic religious education teachers have an immoderate understanding. Therefore, we try to provide assistance that aims, among others; providing assistance related to the understanding of TPQ teachers in the city of Cirebon about strengthening the values of religious moderation through understanding the Qur'an, providing assistance in developing strategies used in instilling religious moderation values to TPQ teachers in the city of Cirebon, and evaluating the results achieved by TPQ teachers after receiving assistance in strengthening the values of religious moderation through understanding the Qur'an. The method used in this service is the Asset Based Community Development method. This community service activity is carried out to support the implementation of the Tri Dharma of Higher Education. The results of this assistance are; appreciative interviews about religious moderation, mapping the potential or assets of the assisted community, establishing cooperation with related institutions (asset mobility link), carrying out seminar activities, and evaluating activities.